In vivo recording of the vestibular microphonic in mammals - Pastras, C.; Curthoys, I.; Brown, Daniel (2017)
Background: The Vestibular Microphonic (VM) has only featured in a handful of publications, mostly involving non-mammalian and ex vivo models. The VM is the extracellular analogue of the vestibular hair cell receptor current, and offers a tool to monitor vestibular hair cell activity in vivo. Objective: To characterise features of the VM measured in vivo in guinea pigs, using a relatively simple experimental setup. Methods: The VM, evoked by bone-conducted vibration (BCV), was recorded from the basal surface of either the utricular or saccular macula after surgical removal of the cochlea, in 27 guinea pigs. Results: The VM remained after vestibular nerve blockade, but was abolished following end-organ destruction or death. The VM reversed polarity as the recording electrode tracked across the utricular or saccular macula surface, or through the utricular macula. The VM could be evoked by BCV stimuli of frequencies between 100 Hz and 5 kHz, and was largest to vibrations between 600 Hz and 800 Hz. Experimental manipulations demonstrated a reduction in the VM amplitude with maculae displacement, or rupture of the utricular membrane. Conclusions: Results mirror those obtained in previous ex vivo studies, and further demonstrate that vestibular hair cells are sensitive to vibrations of several kilohertz. Changes in the VM with maculae displacement or rupture suggest utricular hydrops may alter vestibular hair cell sensitivity due to either mechanical or ionic changes.